1985
DOI: 10.1039/dt9850002541
|View full text |Cite
|
Sign up to set email alerts
|

Lewis-base adducts of Group 1B metal(I) compounds. Part 19. Crystal structures of bis(1,10-phenanthroline)copper(I) perchlorate and dibromocuprate(I)

Abstract: The crystal structures of the title compounds [Cu(phen),] [CIO,] (1) and [Cu(phen),] [CuBr,] (2) (phen = 1,lO-phenanthroline) have been established by single-crystal X-ray diffraction methods at 295 K. Crystals of (I) are monoclinic, P2/c, a = 10.037(3), b = 14.51 8(6), c = 7.672(3) A f3 = 97.82(3)", Z = 2. R was 0.056 for 709 independent 'observed' reflections. Crystals of (2) are monoclinic, C2/c, a = 17.206(4), b = 13.365(2), c = 10.920(3) A, p = 11 5.43(2)", Z = 4. R was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 2 publications
7
31
0
Order By: Relevance
“…As in other bis(phenanthroline)copper(I) complexes, [17,26,27] there are two long Cu-N bonds (to N2 and N4) and two short Cu-N bonds (to N1 and N3) in complex 12 ( Table 2). The inclusion of CuBr 2 -as the counteranion in 12 is similar to that in the cases of [Cu(dpp) 2 ](CuBr 2 ) (10), [16] [Cu(phen) 2 ]-(CuBr 2 ), [28] and the chloride analog [Cu(dpp) 2 ](CuCl 2 ). [20] The CuBr 2 -ion is slightly bent with a Br-Cu-Br angle of 177.2°in 12, which is comparable to the Cl-Cu-Cl angle of 177.3°in [Cu(dpp) 2 ](CuCl 2 ).…”
Section: Copper(i) Complex [Cu(dnp) 2 ](Cubr 2 ) (12)mentioning
confidence: 91%
See 1 more Smart Citation
“…As in other bis(phenanthroline)copper(I) complexes, [17,26,27] there are two long Cu-N bonds (to N2 and N4) and two short Cu-N bonds (to N1 and N3) in complex 12 ( Table 2). The inclusion of CuBr 2 -as the counteranion in 12 is similar to that in the cases of [Cu(dpp) 2 ](CuBr 2 ) (10), [16] [Cu(phen) 2 ]-(CuBr 2 ), [28] and the chloride analog [Cu(dpp) 2 ](CuCl 2 ). [20] The CuBr 2 -ion is slightly bent with a Br-Cu-Br angle of 177.2°in 12, which is comparable to the Cl-Cu-Cl angle of 177.3°in [Cu(dpp) 2 ](CuCl 2 ).…”
Section: Copper(i) Complex [Cu(dnp) 2 ](Cubr 2 ) (12)mentioning
confidence: 91%
“…This is similar to most of the known bis(phenanthroline)copper(I) complexes with aryl substituents in the 2,9-positions of the phenanthroline backbone (maximum absorption in the range 440-470 nm). [32][33][34][35] For 7 and 10, there is a shoulder in the 550-600 nm range, which can be attributed to the distortion of the complex molecule from D 2d symmetry caused by intramolecular π-stacking interactions, as in some known Cu I complexes, for example, [Cu(phen) 2 ]ClO 4 (580 nm) [28] and [Cu(tmp) 2 ]PF 6 (595 nm). [36] This lower-energy shoulder decreases with increasing steric bulk of the ligands (well resolved for 10, much weaker for 11, and disappeared for 12; see Figure 5b), as more sterically demanding ligands may enforce the D 2d symmetry.…”
Section: Uv/vis Spectramentioning
confidence: 96%
“…First, X-ray crystallography studies of OP 2 Cu + have revealed that the dihedral angle between the planar OP rings, though expected to be near 90°in solution, is not stringently fixed (Healy et al, 1985). Variations of the dihedral angle from 49.9°to 80°h ave been observed in the crystal state.…”
Section: A Model Of Op 2 Cumentioning
confidence: 97%
“…These sugars form the pair of sugars of the two strands most sensitive to DNA conformational effects on OP 2 Cu + activity (Drew & Travers, 1984). Due to the small size of OP 2 Cu + (Healy et al, 1985), the sequence of three to four base-pairs between opposing sugars is precisely of the size expected for the OP 2 Cu + -DNA interaction domain. This basepair sequence is the one directly accessible upon binding to the minor groove ( Figure 1).…”
Section: Thermodynamic Analysismentioning
confidence: 99%
“…1, b). 13 The estimation of the minimum van der Waals thickness of a single layer of the complexes localized in the interlayer space of MoS 2 (layer thickness of intercalant ∆c), which was performed using the structural data for these com plexes, 11,13 gives ∆c of ~6-7 and 5-5.5 Å for layered compounds with complexes I and II, respectively. The orientation of the C 2 axes of both complexes perpendicu larly to the MoS 2 layers corresponds to these thickness values (see Fig.…”
Section: Resultsmentioning
confidence: 99%